MENGUAK NILAI-NILAI RITUAL ACCERA KALOMPOANG SEBAGAI PENOLAK BALA MASYARAKAT GOWA - Mr Agusdi; Muhammad Bahly Basri; Nursaddang Al Ashar; Mrs Hasni (Rayhan Intermedia, 2019)
Culture that develops in society contains values. These values​are used as guidelines adopted by each member of the community, especially in attitude and behavior and become a benchmark for assessing or observing how individuals and groups behave. This research was conducted to find out the meanings contained in the implementation of the Accera Kalompoang ritual and find out the impact on the community on the implementation of the Accera Kalompoang ritual as a repellent. The type of research used in this study is qualitative research with an ethnographic approach. This activity is divided into 3 stages, namely the initial stage (preparation), the implementation phase, and the final stage. Informants in this study were the people who lived around the traditional Balla Lompoa house, Gowa Regency Consultant / Culture, and the traditional head of the Gowa kingdom. The results of this study, namely the Accera Kalompoang ritual contain historical, spiritual, and fraternal meaning or friendship. The impact of the Accera Kalompoang ritual has a positive impact on the community, namely as a repellent and giving economic benefits during the ritual implementation. In addition, there is a negative impact if the Accera Kalompoang ritual is not carried out, such as a prolonged drought.